The effect of circuit weight training under ultraviolet B rays as vitamin D supplementation in preventing COVID-19 - Miftahul Zannah; Isidore Jehaman (Universitas 'Aisyiyah Yogyakarta, 2022)
The body's immune stability is essential by increasing fitness through exercise and getting enough vitamin D from ultraviolet B rays from sunlight. The exercise that is carried out, namely circuit weight training, is a mechanical exercise that can be applied outdoors to get exposure to ultraviolet B rays as a natural source of vitamin D. Exposure to sunlight is the best source of vitamin D for the synthesis of vitamin D from pre-vitamin D which is found under the skin. UVB rays (290 – 315 nm) originating from the sun will be absorbed by the skin and will then convert 7-dehydrocholesterol in the skin to pre-vitamin D3 which is then converted to vitamin D3 to be processed in the liver into 25(OH)D and in the kidneys into 1,25(OH)2D3. The purpose of this study was to determine the effect of circuit weight training under ultraviolet B rays as vitamin D supplementation in preventing Covid-19. Associated with the severity of Covid-19 occurred because reduced vitamin D supplementation could be used as a better control of SARS-COV-2. This research method was a quasi-experimental design with a pretest-posttest with a control group on 80 subjects with a ratio of 1:1 for each group. Test the normality of normally distributed data. Hypothesis analysis found a significant effect on vitamin D levels (p=0.001) circuit weight training exercise under UV-B light sourced from sunlight and there was no significant effect on increasing vitamin D levels (p=0, 710) with circuit weight training exercises performed not under UV-B rays from sunlight. This study states that there is an effect of circuit weight training under ultraviolet B rays as vitamin D supplementation in preventing Covid-19.